A compact digital time differential perturbed angular correlation-spectrometer using field programmable gate arrays and various timestamp algorithms - Jäger, Markus; Iwig, Kornelius; Butz, Tilman (Review of scientific instruments, 2011)
A user-friendly fully digital time differential perturbed angular correlation (TDPAC)-spectrometer with six detectors and fast digitizers using field programmable gate arrays (FPGA) is described and performance data are given. The new spectrometer has an online data analysis feature, a compact size, and a time resolution such as conventional analog spectrometers. Its calculation intensive part was implemented inside the digitizer. This gives the possibility to change parameters (energy windows, constant fraction trigger delay) and see their influence immediately in the γ - γ correlation diagrams. Tests were performed which showed that the time resolution using a 60 Co source with energy window set at 1.17 MeV and 1.33 MeV is 265 ps with LaBr 3 (Ce) scintillators and 254 ps with BaF 2 scintillators. A true constant fraction algorithm turned out to be slightly better than the constant fraction of amplitude method. The spectrometer performance was tested with a TDPAC measurement using a 44 Ti in rutile source and a positron lifetime measurement using 22 Na. The maximum possible data rate of the spectrometer is 1.1 × 10 6 γ quanta per detector and second.